MEASUREMENT OF CUSTOMER PROFITABILITY AND ANALYSIS OF CUSTOMER CHARACTERISTICS AT PT Z: A CASE STUDY OF AN ENERGY DISTRIBUTION COMPANY - Priyo Sembodo; Evony Silvino Violita (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to measure customer profitability and analyze customer characteristics at PT Z, a state-owned enterprise operating in the energy distribution sector. Despite continuous growth in the number of customers, PT Z has experienced fluctuating profitability, indicating the need for a more granular, customer-level financial analysis. This research adopts a quantitative case study approach complemented by qualitative insights. Customer Profitability Analysis (CPA) is applied by systematically allocating revenues and operating costs to different customer segments using an Activity-Based Costing (ABC) approach, with electricity sales volume (kWh sold) as the primary cost driver. Customer characteristics are further analyzed based on three dimensions: profitability, significance, and strategic value. The results reveal that customer profitability at PT Z is highly heterogeneous and strongly influenced by installed capacity, consumption intensity, and tariff structure. Medium- to large-capacity customers with tariffs close to economic pricing consistently generate positive profits, while low-capacity customers across most segments tend to produce negative profit margins. Customer mapping based on the strategic, significant, and profitable dimensions shows that Type A customers—those that are strategic, significant, and profitable—represent the main value drivers of the company. Conversely, several strategic and significant customer groups remain unprofitable, reflecting the impact of regulated tariffs and public service obligations. Overall, this study demonstrates that customer profitability analysis is a crucial strategic tool for improving value-based customer management in the energy distribution industry. The proposed model provides PT Z with a more accurate basis for resource allocation, service differentiation, and policy evaluation, enabling the company to balance financial sustainability with regulatory and social responsibilities.